Adaptive PWM algorithm using digital-signal processing based THD measurement for electric vehicle application - Jaehoon Baek; Seung-duck Choi; Sangshin Kwak (2014 IEEE Applied Power Electronics Conference and Exposition - APEC 2014, 2014)
This paper presents an advanced pulse width modulation (PWM) method with cross-correlation-based digital signal processing for electric vehicle (EV) application. The algorithm is designed to adaptively apply PWM techniques depending on motor operating conditions: space vector PWM (SVPWM) method in the high total harmonic distortion (THD) condition and the discontinuous PWM (DPWM) method in the low harmonics operating condition of an EV motor. The phase current of EV motor changes by the torque command and the THD requirements to be calculated in real time to select PWM method. Proposed simple cross-correlation-based THD calculation presents minimal computation load and short convergence time to apply a real-time adaptive PWM algorithm for EV traction inverter. Experimental verification of proposed algorithm is performed by using 80kW Permanent Magnet (IPM) Motor setup.